Higher education and civic engagement international perspectives - McIlrath, Lorraine; MacLabhrainn, Iain (Corporate social responsibility series, 2007)
Bringing together an international team of contributors, this volume provides an original and powerful contribution to debates about the civic purpose of higher education. It suggests that universities can best realize their civic mission by making it central to their policy and practice.